(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2025)
In this article, it was noted that in the process of teaching physics, various types of independent work are used. Formation learners’ ability to work independently with educational and additional literature, schoolchildren’ independent homework in physics as necessary elements of the educational process.